Respuesta :

Answer:

The answer is "C" f(x)= x+ 4 and g(x)= x^3 - 1

Step-by-step explanation:

all you have to do is replace the x in "G" with the "F" function

Answer:  Choice C

F(x) = x+4  and  G(x) = x^3-1

===========================================================

Explanation:

Let's try choice A to see if it works or not

G(x) = (x+4)^3

G( F(x) ) = ( F(x)+4 ) ^3 .... replace every x with F(x)

G( F(x) ) = ( x-1+4 ) ^3 .... plug in F(x) = x-1

G( F(x) ) = (x+3)^3

This isn't the same as (x+4)^3 - 1. You can confirm this with a graph or a table of values. We cross choice A off the list.

------------

Let's try choice B

G(x) = x+4

G( F(x) ) = F(x)+4

G( F(x) ) = x^3-1 + 4

G( F(x) ) = x^3 + 3

Similar to choice A, this isn't the same as (x+4)^3-1. We can cross this off the list as well.

--------------

Now choice C

G(x) = x^3 - 1

G( F(x) ) = ( F(x) )^3 - 1

G( F(x) ) = (x+4)^3 - 1

We found the final answer.